Performance of The Village Goverment in Implementing The Village Information System Program in Sungai Bawang Village - sujianto; Anisa, Siti (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2020)
The performance of the Sungai Bawang Village Government in the Village Information System program can be seen from the implementation process. This study focuses on the performance of the Sungai Bawang village government in the Village Information System Program in order to realize the vision and mission of Kuantan Singingi Regency. But the realization in the field that the performance of the Sungai Bawang village government in the Village Information System program did not have a significant impact. In terms of productivity indicators, after the implementation of the Village Information System program the performance of the Sungai Bawang Village Government did not change significantly. Indicators of service quality, the quality of services received by the community before and after the implementation of the Village Information System program have no real impact, because the services provided are still the same, still not based on online information technology. Indicator of responsiveness can be seen that third parties are not committed to the agreed work contract agreement. Responsibility Indicator, the standard used as a reference in implementing the Village Information System program is Kuantan Singingi District Regulations No. 57 of 2017 concerning Village Information Systems and their derivatives namely Standard Operating Procedure (SOP) for Village Information Systems. Accountability indicators, there is an element of political interest in the Village Information System program. The purpose of this study was to determine the performance of the Sungai Bawang village government in the implementation of the Village Information System program and its inhibiting factors. The research method uses qualitative by emphasizing the concept of performance measurement. The techniques used in collecting data are observation, interviews, documentation, and literature. The results showed that the performance of the Sungai Bawang village government was still not optimal. The inhibiting factor is the non-commitment of the third party in carrying out the responsibility, the Village Information System program is influenced by the political interests of certain groups so that the Village Information System program does not run as contained in Kuantan Singingi No. 57 of 2017 concerning Village Information Systems.